ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN BISNIS INDONESIA CORPORATE SOCIAL RESPONSIBILITY AWARD (BISRA) DAN DAMPAKNYA PADA ABNORMAL RETURN ANTAR SEKTOR INDUSTRI - Budi Darmawan, Susilo; Nila Puspita , Lisa Martiah (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
This research is motivated by the lack of clarity in the literature regarding the influence of CSR awards (BISRA) on abnormal returns, especially in various industrial sectors. This study aims to evaluate the impact of the BISRA award announcement on the abnormal returns of companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. An event study approach was used with a sample of 33 companies from 84 BISRA award recipients, selected based on inclusion and exclusion criteria. The Wilcoxon Signed Rank Test and One Sample T-Test were conducted to test changes in abnormal returns before and after the BISRA announcement. The results showed that on most days during the BISRA announcement, there was no significant return, and the impact of the BISRA award announcement on abnormal returns as a whole did not show significant differences in each award recipient industry sector. The implications of this study suggest that factors such as industry sector and market perception play a role in influencing market reactions to CSR awards.